2009
DOI: 10.1021/ja906055m
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Directed Localization and Orientation of a Functional Foreign Transmembrane Protein within a Silica Nanostructure

Abstract: A simple procedure for introducing functional exogenous membrane-bound proteins to viable cells encapsulated within a lipid templated silica nanostructure is described. In one method, bacteriorhodopsin (bR) was added directly to a Saccharomyces cerevisiae solution along with short zwitterionic diacylphosphatidylcholines (diC(6) PC) and mixed with equal volumes of a sol precursor solution. Alternatively, bR was first incorporated into liposomes (bR-proteoliposomes) and then added to an S. cerevisiae solution wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…In that case, preserving the viability of cells within sol-gel derived hybrid matrices appears to be a real challenge. Studies pioneered by Livage et al 331 and confirmed by other groups [332][333][334][335] indicating that encapsulated bacteria (E. coli) can survive the gelation procedure and remain able to continue normal metabolic activity within the gel matrix are opening new promising avenues in this field. 326-332…”
Section: Biohybrids Made By Sol-gel As Reviewed Bymentioning
confidence: 96%
“…In that case, preserving the viability of cells within sol-gel derived hybrid matrices appears to be a real challenge. Studies pioneered by Livage et al 331 and confirmed by other groups [332][333][334][335] indicating that encapsulated bacteria (E. coli) can survive the gelation procedure and remain able to continue normal metabolic activity within the gel matrix are opening new promising avenues in this field. 326-332…”
Section: Biohybrids Made By Sol-gel As Reviewed Bymentioning
confidence: 96%
“…The first in vitro biomimetic synthesis of silica was reported more than a decade ago 19 . Later this biomimetic approach was used in producing silica nanomaterials 20 21 22 and cell-directed silica biocomposites 17 23 24 25 26 27 . SBR is a self-limiting biomolecular surface-directed silica assembly process that results in nearly an exact replica of external and internal cellular 17 27 , tissue, and organism-scale 18 features in nanometre (<10 nm) thick silica layers.…”
mentioning
confidence: 99%
“…The authors suggest that these molecules maintain bacteria in a stationary state and modify their metabolism in order to enhance cell resistance to the external stresses [58]. Recently, a promising pathway to cell encapsulation has been reported by Brinker et al [60][61][62]. Different bacteria cell lines (and even yeasts) have been incorporated within nanostructured silica films formed by an evaporation-induced self assembly approach (Fig.…”
Section: Bacteriamentioning
confidence: 99%